IT Management Culture and Strategic Alignment in the Era of Digitalization - Sieber, Marcel Roland; Malý, Milan, 1936-; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The goal of this thesis is to explore the organizational culture of IT management and its relation to the strategic alignment of business and IT in the digital age. Business-IT alignment is one of the crucial concerns of IT management. This thesis assumes that such an alignment is strongly associated with certain IT management culture types. It examines this assumption through a systematic literature review, a case study, and a survey. The literature review discovered a knowledge gap in organizational culture research regarding business-IT alignment. The case study illuminated this gap by combining the competing values framework and the strategic alignment model. Finally, a questionnaire investigated the IT management culture types, the strategic alignment perspectives, and the organizational characteristics of digitalization. The results confirm the interrelation between IT management culture and business-IT alignment. First, business units expect IT management to provide a secure, efficient, and effective IT infrastructure. Consequently, IT management with a hierarchical culture performs best as the strategic alignment perspective of a service center. Second, innovative thinking and change readiness are also valued. This is where the performance criteria of the strategic alignment perspective as an investment center are most evident. Finally, the organizational characteristics of digitalization moderate these relationships.
Vedoucí práce: Milan Malý
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations